KONSEP HANNAH ARENDT TENTANG POLITIK SEBAGAI PEMBICARAAN DAN KONTRIBUSINYA DALAM MENYIKAPI PLURALITAS PANDANGAN - Yosef Keladu Koten (Institut Filsafat dan Teknologi Kreatif Ledalero, 2019)
Abstract: Differences in views in a plural community cannot beavoided because each view or philosophy of life is formulated byreasonable people. It is generally accepted that the plurality oflife views must be addressed in the spirit of democracy that relieson the use of reason, where each person or group is given theopportunity to convey their perspectives. But the fact shows thatthe role of reason is getting weaker in deliberation, especially incountries that implement a system of representative democracy.Then, do we thus abandon democracy as an approach in addressingdifferences of opinion? Using a qualitative approach, the authorargues that democracy remains the best choice in addressingdifferences of views. However, based on Arendt’s concept ofpolitics as a speech, the ideal democratic approach should bedeliberative rather than liberal because deliberative democracyaims to transform the perspective of each person or grouhlm.Keywords: politics, pluralism, common sense, agonistic, liberaldemocracy, deliberative democracy, political speech.